HUBUNGAN MUSLIM DENGAN NON-MUSLIM PERSPEKTIF ULAMA BUGIS - Muhammad Yusuf (AL-TAHRIR, 2014)
Qur’anic exegeses have many variants in terms of sources, methods and languages. Some Qur’anic exegeses using tah}li>li> or mawd}u>’>i method are even written in a local language. This article elucidates the Bugese Muslim scholar thoughts in their work Tafsere Akorang Mabbasa Ugi regarding Muslim and Non-Muslim relations. Using historical approach and content analysis, the author traces the thematic Qur’anic verses on Muslims and non-Muslim relations and the actual practices of interactions between the Prophet Muhammad and non-Muslims. It shows that the verses do not limit interactions and cooperation in the name of religion. Such interactions are limitless to non-Muslims. The acknowledgment on the existence of others and the prominence in ethical attitudes towards them are keywords in maintaining harmonious and tolerant interreligious communication and relations. There are universal and particular values of religion. While the universal values serve as a common denominator for all religions, the particular values are specific to each religious tradition that must be fully tolerated and respected because these are sensitive aspects that may stimulate conflicts.